(677) Current State and Development Possibilities of the Money Market in African Countries (The Case of the UAR) الوضع الراهن وإمكانيات تطوير سوق المال في الدول الأفريقية (حالة جمهورية أفريقيا الوسطى) - M. El-Imam, M. (INP, 2023)

(untitled)
Paper Submitted at the Seminar for Teachers and Research Workers in African Universities and Research Institutions / Dakar July 19-25 1966